CONFRONTING FOND MEMORIES OF APARTHEID - Truscott, Ross (PINS-Psychology in Society, 2025)
Dlamini, Jacob (2009) Native nostalgia. Auckland Park: Jacana. ISBN 978-1-77009-755-1. Pages 169. Being nostalgic for apartheid in post-apartheid South Africa is frequently equated with being politically insane and morally questionable. In his recent book, Native nostalgia, Jacob Dlamini seeks not only to retrieve memories of the struggle against apartheid - memories that would be quite compatible with the anti-apartheid, post-apartheid national narrative - but to describe his nostalgia for apartheid itself, including life within the very instruments of the apartheid regime. Dlamini remembers his childhood in Katlehong, an apartheid township on the East Rand, positively, recalling scenes related in complex ways, to Bantu Education, ethnic radio, the relative order of the apartheid township and the Afrikaans language. These are memories, as Dlamini notes, which run contrary to the accepted notion that under apartheid, all blacks only suffered, and suffered in the same way.